2015
DOI: 10.1021/acs.nanolett.5b03515
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Group IV Nanophotonic Structures Incorporating Diamond Silicon-Vacancy Color Centers

Abstract: We demonstrate a new approach for engineering group IV semiconductor-based quantum photonic structures containing negatively charged silicon-vacancy (SiV − ) color centers in diamond as quantum emitters. Hybrid SiC/diamond structures are realized by combining the growth of nanoand micro-diamonds on silicon carbide (3C or 4H polytype) substrates, with the subsequent use of these diamond crystals as a hard mask for pattern transfer. SiV − color centers are incorporated in diamond during its synthesis from molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 48 publications
0
49
0
3
Order By: Relevance
“…29 To see if it is essential to tailor the adamantane molecule to be effective for chemical nucleation, further experiments with adamantane and 1-mercaptoadamantane(C 10 H 16 S) dissolved in cyclohexane were conducted along with studies of the effects of solvents like toluene and cyclohexane on the crystal density through the use of the low temperature incubation step. Furthermore, while previous studies have dissolved tailored diamondoids in solvents such as toluene 16 it needs to be seen if such chemicals can also give rise to nucleation sites. Four samples were therefore spin-coated with various chemical precursors and then exposed to CVD with the process detailed previously (low temperature incubation for 30 min followed by high temperature growth for 60 min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 To see if it is essential to tailor the adamantane molecule to be effective for chemical nucleation, further experiments with adamantane and 1-mercaptoadamantane(C 10 H 16 S) dissolved in cyclohexane were conducted along with studies of the effects of solvents like toluene and cyclohexane on the crystal density through the use of the low temperature incubation step. Furthermore, while previous studies have dissolved tailored diamondoids in solvents such as toluene 16 it needs to be seen if such chemicals can also give rise to nucleation sites. Four samples were therefore spin-coated with various chemical precursors and then exposed to CVD with the process detailed previously (low temperature incubation for 30 min followed by high temperature growth for 60 min).…”
Section: Methodsmentioning
confidence: 99%
“…It is to be noted that in many of the previous studies on the chemical nucleation of diamond growth the diamondoid molecules were spun-coated on substrates by dissolving in solvents like glycol 15 or toluene. 16 Therefore, it is important to investigate the effects these solvents have on the nucleation density on the substrates. For example, in the course of the present study, it was found that solvents like toluene or cyclohexane can also lead to enhanced nucleation on silicon substrates, in agreement with results reported within previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Внедряясь в решeтку алмаза, атомы Si стимулируют образование вакансий в соседних узлах решeтки, что приводит к формированию точечных дефектов -опти-чески активных центров SiV. Отметим, что существует также возможность контролируемого введения центров окраски SiV в алмаз путeм добавления силана в рабочую газовую смесь как источника примесных атомов Si в процессе химического газофазного осаждения частиц [9,11,12,15,18,19,34], Cr-содержащих центров [26,27], и сравнима с шириной БФЛ одиночных центров окраски SiV в алмазе [13,20]. В спектрах исследованных на-ноалмазов практически отсутствует фоновой сигнал в виде широкой полосы ФЛ с максимумом в видимой области спектра, которая характерна для различных гетероэпитаксиальных алмазов [10,11,15].…”
Section: экспериментальные результаты и их обсуждениеunclassified
“…В спектрах наблюдается БФЛ ансамбля центров SiV с максимумом на длине волны ∼ 736.8 nm. В соответствие с четырeхуровне-вой электронной структурой центра SiV его БФЛ при температуре жидкого гелия имеет тонкую структуру и состоит из четырeх линий, образовавшихся из-за расщепления основного и возбуждeнного состояний центра SiV [11,13,[16][17][18]41]. Неоднородное уширение из-за присутствия остаточных напряжений в наноалмазе приводит к замыванию линий тонкой структуры [11,13].…”
Section: экспериментальные результаты и их обсуждениеunclassified
See 1 more Smart Citation